IS TOEFL SUBJECT NECESSARY FOR ENGLISH EDUCATION STUDY PROGRAM? LECTURERS’ PERSPECTIVE - Benni Ichsanda Rahman Hz (UIN Sumatera Utara, 2021)
This study attempts to investigate the lecturer’s perspective, whether TOEFL subject is necessary for English education study program or not. This study is a case study approach that is naturally qualitative. The study involved three lecturers of English Education Study Program as participants.. This study was conducted at one State University on North Sumatera, Indonesia, majoring in English Education. The participants were interviewed through interview via telephone. The lecturers were asked and interviewed about their opinions about the existence and the implementation of TOEFL subjects in the study program. The data were analyzed by using percentage calculation. After the participants answered the interview, the data were then classified according to its origin. The respondents have different perspective on this study. Two respondents stated that TOEFL should not be included as a subject to be studied by the English Education students in case TOEFL is tips and trick skill based, not knowledge base. In contrary, one of the respondent stated that TOEFL is required to be added to the curriculum, in case the students have not understood all aspects in reading which then TOEFL should be learned by students in specific credit subject.